Απομάκρυνση ενδοκρινικών διαταρακτών με τη μέθοδο της φωτοκατάλυσης της τιτάνιας - Κωμοδρόμου, Στέλλα (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The purpose of the study was the removal of endocrine disrupters from treated wastewater with titanium dioxide (titania) photocatalysis. The compounds studied were parachlorophenol, 2,4-dichlorophenol, 2,3,4-Trichlorophenol, ethinyl estradiol, 17β estradiol, estrone, bishepnol A, carbamazepine, iminostilbene, stanolone, androsterone, triclosan, norethindrone και 2,4-d-t-butylphenol. The objective of the study was to identify the optimum experimental conditions for maximum contaminant removal in treated waste water sample. The study intended in the better simulation with the conditions in a water treatment plant. For this reason, the substances were not treated separately, but in a mixture, the starting concentrations were based on the concentrations of substances detected in water treatment plants. Photocatalysis experiment were conducted in a cylindrical reactor under the effect of UVA radiation (LP lamp, by Philips) at a concentration of titania 0,5 g/L. The procedure followed, was addition of the catalyst in the mixture of endocrine disrupters and waiting for 30 minutes in the dark, for the calculation of the amount of substances adsorbed to the catalyst. The solution was then exposed to ultraviolet radiation and was sampled at the following times 30, 60, 120, 180, 240, 360 and 720 minutes of radiation. After was, microextraction of the substances with SPME fiber and introducing the fiber into a gas chromatograph mass spectrometry (GC-MS) for separation and detection of substances took place. The method followed was quite efficient since the substances were separated, the detection limits of the substances were 0,0128 to 0,9189 μg/L and quantification 0,0641 to 1,9147 μg/L. Some of the substances experienced high adsorption in the catalyst (overall percentage of adsorption: 1,20% - 87,10%). The difference in adsorption are based on the charge and the size of the substances, the pore size of the catalyst and its relatively high concentration compared with the concentrations of substances (six orders of magnitude). Most of the endocrine disrupters were removed in large proportion (66,57% - 98,98%), while some were removed beyond the method detection limit. Natural hormones were completely removed except of estradiol that its concentration was increased as it is product of oxidation of 17β estradiol. The chlorophenols removed successfully, as well as the pharmaceuticals compounds. The results on the photocatalytic degradation of the endocrine disrupters triclosan, norethindrone, 2,4-dt-butylphenol, stanolone and androsterone were inconclusive, possibly due to analytical limitations (inadequate adsorption/desorption of the compounds from the fiber) that resulted in false measurements at the selected sampling events.
Keywords: Endocrine disrupters; Photocatalysis; T1O2; Aquatic ecosystems pollutants; Waste water treatment; Απομάκρυνση ενδοκρινικών διαταρακτών; Φωτοκατάλυση; Σταθμός επεξεργασίας λυμάτων; Υδάτινα οικοσυστήματα ρύπων